The Attitude of Mobile Users on Mobile Marketing: Case Study on Fast Food Restaurant at Bukit Bintang - Mohd Nazari Nazari, Norwani; Faiq Bin Abdul Fattah, Mohd; Binti Zainuddin, Zalina; Binti, Haslina (International Journal of Engineering and Technology, 2018)
Mobile marketing is increasing popularity despite, it is not fully utilized in fast food restaurant. The objective of the study are, firstly to examine customer attitude toward mobile marketing, secondly to assess the perceptions that influence attitude towards mobile marketing, thirdly to identify significant relationship between attitude and mobile marketing promotional tools, and forth, to evaluate the effectiveness of mobile marketing as promotional tool. The study area is in Bukit Bintang, Kuala Lumpur conducted over sample of 384 respondents. Triangulation methodology of both qualitative and quantitative methods including survey questionnaire, field observation, telephone and face to face interview are used in this study. The finding shows there is favorable attitude towards mobile marketing in the customer population, gauging actual use of mobile marketing of fast food restaurant. The perceptions influencing the attitude are Perceived Usefulness (PU), Perceived Ease of Use (PEU) and Mobile Phone Self-Efficacy (MSE). The underlying motives influencing use of mobile marketing of fast food restaurant are Speed, Functionality, Customer Friendly and Hospitality. Ranges of promotional tools in mobile phone have significance relationship with attitude and effective to achieve marketing goal such as increase sales and market growthÂ for fast food restaurant.Â